The Pollution Effects of Mergers and Acquisitions: Asymmetry, Disaggregation, and Multilateralism - Julia Swart; Charles van Marrewijk (Tinbergen Institute, 2011)
This paper studies the impact of cross-border Mergers and Acquisitions (M&As) on Carbon Dioxide emissions. Carbon Dioxide is the main anthropogenic greenhouse gas. A global problem that requires a multilateral solution. To take this into account we introduce an institutional variable, which captures the degree of international commitment to decrease and control the degradation of the environment. We test three hypotheses and find: (i) Asymmetry: the development level of the target country determines the direction of the effect of M&As on CO2 emissions; (ii) Sector-specific impact: pollution intensive sectors have an impact on CO2 emissions, whereas other sectors do not; (iii) Multilateralism: multilateral agreements are important to reduce CO2 emissions.
Keywords: F23; Q55; Q56; 330; Carbon Dioxide Emission; Mergers and Acquisitions; Foreign Direct Investment; Institution; Environment; Luftverschmutzung; Treibhausgas-Emissionen; Auslandsinvestition; Übernahme; Institutionelle Infrastruktur; Vergleich; Welt